2022
DOI: 10.1051/meca/2022017
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of the influence of the relative humidity of leaves and their link to adhesion losses in the wheel-rail contact

Abstract: Every autumn, low levels of wheel–rail contact adhesion caused by leaves on the railhead surface are reported by train drivers. These incidents cause problems for the safety and regularity of rail traffic and occur predominantly at the beginning and end of the day when high humidity levels are achieved. At those moments the air temperature reaches the dew point temperature creating moisture on the railhead and oxides which react chemically with dead leaves found on the railhead surface. This article presents t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…The presence of worn and said 3BL causes the traction coefficient to drop less at the beginning and have a steeper increase. Similar observations and conclusions were made by the authors who have tested the traction recovery aspects of a leaf-contaminated rail environment [24][25][26]. This makes it essential to understand traction recovery in the presence of wear and naturally generated 3BL.…”
Section: Leaf-typesupporting
confidence: 73%
See 1 more Smart Citation
“…The presence of worn and said 3BL causes the traction coefficient to drop less at the beginning and have a steeper increase. Similar observations and conclusions were made by the authors who have tested the traction recovery aspects of a leaf-contaminated rail environment [24][25][26]. This makes it essential to understand traction recovery in the presence of wear and naturally generated 3BL.…”
Section: Leaf-typesupporting
confidence: 73%
“…However, the ANOVA analysis performed by the researchers suggests no significant influence in the interaction between the amount of leaves and humidity but indicates individual factors alone have significance. Similarly, Guidoum et al [24] have experimentally studied the tribological aspects of leaves in the presence of moisture. They have concluded that the slip rate and percentage humidity strongly influence adhesion.…”
Section: Introductionmentioning
confidence: 99%
“…A nominal slip of 3% was used with the intention of creating the layer more effectively as higher slip values might accelerate the development of leaf layers. 31 Images from the layer creation are shown in Figure 2. The ambient conditions were 20.1°C and a relative humidity of 51%.…”
Section: Methodsmentioning
confidence: 99%
“…12 Many researchers have conducted studies to investigate the effect of 3BL on wheel-rail adhesion. [13][14][15][16] Khan 17 studied the effect of third bodies on friction and wear at the wheel-rail interface using a handheld tribometer. Meierhofer 18 introduced the definition of 3BL into the creep force model and compared the results with experimental results at large creepages.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have noted that the decrease in the adhesion‐creepage curve was mainly attributed to the change of shear stress caused by temperature in the third body layer (3BL) 12 . Many researchers have conducted studies to investigate the effect of 3BL on wheel‐rail adhesion 13–16 . Khan 17 studied the effect of third bodies on friction and wear at the wheel‐rail interface using a handheld tribometer.…”
Section: Introductionmentioning
confidence: 99%